2017
DOI: 10.1021/acsomega.7b00335
|View full text |Cite
|
Sign up to set email alerts
|

Ru(II)-Catalyzed Regiospecific C–H/O–H Oxidative Annulation to Access Isochromeno[8,1-ab]phenazines: Far-Red Fluorescence and Live Cancer Cell Imaging

Abstract: A facile ruthenium(II)-catalyzed regiospecific C–H/O–H oxidative annulation methodology was developed to construct isochromeno[8,1-ab]phenazines. This methodology delivers various advantages, such as scope for diverse substrates, tolerance to a range of functional groups, stability under air, and yields regioselective products. This methodology was successfully applied to synthesize far red (FR) fluorescent probes for live cancer cell imaging. The synthesized compounds displayed notable fluorescence properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Over the past decades, multicolor fluorescent materials have received extensive attention, because of their potential applications in the next-generation lighting sources and displays, as well as in optical imaging agents to decipher biological events. To prepare multicolor fluorescent molecules, chemists have generally synthesized fluorophores from various precursors, or frequently, under different reaction conditions. Sometimes one must use even totally different synthetic pathways, because of a lack of versatility of synthetic scheme.…”
mentioning
confidence: 99%
“…Over the past decades, multicolor fluorescent materials have received extensive attention, because of their potential applications in the next-generation lighting sources and displays, as well as in optical imaging agents to decipher biological events. To prepare multicolor fluorescent molecules, chemists have generally synthesized fluorophores from various precursors, or frequently, under different reaction conditions. Sometimes one must use even totally different synthetic pathways, because of a lack of versatility of synthetic scheme.…”
mentioning
confidence: 99%
“…In 2017, Perumal and co-workers synthesized a series of far red (FR) fluorescent probes, isochromeno[8,1- ab ]phenazine derivatives that displayed exciting fluorescence properties, both in solution phase and in thin films (Scheme 33 ). 131 The obtained fluorophores showed prominent FR fluorescence with high quantum yield, and exhibited better cell imaging properties, with excellent biocompatibility. The regioselective synthesis followed the similar protocol to that depicted in Scheme 32 involving ruthenium(II)-catalyzed C–H activation and subsequent annulation with alkynes.…”
Section: C–h Activation Pathways In the Creation And Modification Of ...mentioning
confidence: 96%
“…It was found that the catalyst could be recovered and used again by adding norbornadiene at the end of the reaction . The Ru(II)‐catalyzed C−H/O−H activation and annulation reactions were also utilized for the synthesis of isochromeno[8,1‐ ab ]phenazines which displayed remarkable fluorescence properties in solution and as a thin film (Scheme ) …”
Section: Introductionmentioning
confidence: 99%